Violence on street children: Looking through Erikson’s psychosocial development theory - Elma Kaiser (Journal of Health and Social Sciences)
Poverty, family breakdown, neglect, abuse or abandonment, are the common triggers for children to run away or be forced to leave their homes. This is a common phenomenon across the globe. While trying to survive on the streets, the children are often re-exposed to violence. To survive on the street, they must make decisions with significant implications for life, which is not usual for a child and or adolescents. Erikson, the developmental psychologist and psychoanalyst, explains development as a lifelong project, proceeding from birth to death through the eight psychological stages. It is important to understand the life stages and the distinctive characteristics that comes along. However, it is also important to understand the life stages of street children which do not always align with the theory. This article aims to depict a global picture of street children. The examples from various parts of the world regarding the reason for moving to the streets and violence that they encounter. Furthermore, this paper looks through the lens of Erik Erikson’s psychosocial development theory and describe how these experiences can shape the life stages of street children. There are stark contrasts between the parameters of the theory when compared with children with conventional settings and the children living in an unprotected environment.